Clavate Tortoise Beetle, Plagiometriona clavata (Fabricius) (Insecta: Coleoptera: Chrysomelidae) - Robert E. Woodruff (EDIS)
EENY-392, a 3-page illustrated fact sheet by Robert E. Woodruff, describes this common tortoise-shaped beetle which prefers host plants in the family Solanaceae. Includes sections on synonymy, distribution, description, hosts and biology, and selected references. Published by the UF Department of Entomology, October 2006.